20.8k views
3 votes
Complete the factorization of 4x2 – 9.



4x2 – 9 = ( x – )( x + )

User Basbous
by
4.8k points

2 Answers

5 votes


\huge{ANSWER}


{2x}^(2) - {3}^(2)

so by identity


{a}^(2) - {b}^(2) = (a + b)(a - b)

(2x+3)(2x-3)✔✔✔

User Ellis Michael
by
4.7k points
1 vote

Answer:


\large\boxed{4x^2-9=(2x-3)(2x+3)}

Explanation:


4x^2-9\\\\METHOD\ 1:\\\\4x^2+6x-6x-9=2x(2x+3)-3(2x+3)=(2x-3)(2x+3)\\\\METHOD\ 2:\\\\\text{use}\ a^2-b^2=(a-b)(a+b)\\\\4x^2=2^2x^2=(2x)^2\\9=3^2\\\\4x^2-9=(2x)^2-3^2=(2x-3)(2x+3)

User Berker
by
5.1k points